Extinction during time controlled direct retinal stimulation after recovery from right hemispheric stroke. Issue 5 (November 1995) - Kaplan, R F; Cohen, R A; Rosengart, A; Elsner, A E; Hedges, T R; Caplan, L R
Abstract : The temporal variables of extinction in two patients with right hemispheric stroke and two normal controls were studied using a scanning laser ophthalmoscope (SLO). This instrument enabled eye movements to be controlled for by projecting time controlled stimuli directly on to the retina. Both patients had recovered from their stroke (four months and five years) and seemed clinically normal. At 50 ms, patient 1 extinguished one of two stimuli on seven of 40 double simultaneous stimulation (DSS) trials (five left, two right) and patient 2 extinguished the left stimulus on every DSS trial. At 100 ms, patient 1 performed almost perfectly, whereas patient 2 extinguished on 30% of the DSS trials (10 left, two right). At 200 ms, patient 2 performed perfectly. Neither of the controls showed extinction to DSS at any presentation time. Thus detecting DSS was time dependent in the patients but not the normal subjects. These data support the theory that recovery from neglect after right hemispheric damage may be mediated by the left hemisphere.